Proposta de modelo para operacionalizar a transformação digital com base nas competências em gerenciamento de projetos e tecnologias digitais - Gonçalves, Marcelo Luiz do Amaral (2022)
Digital transformation (DT) is a subject that has aroused great interest among scholars and practitioners. This is because digitalization brings great challenges to companies in the incorporation of digital technologies, as well as requires cultural and process changes to carry out the change. In addition, such changes require companies to consider the realignment of strategies for the changes arising from TD, adapting the organization and creating new business models to meet digital demands, generating value and remaining competitive. In this sense, project management (PM) has proved to be a fundamental element as a strategic support, helping to structure, organize and execute the changes involved in DT. Thus, this study has the general objective of developing a model to help companies operationalize the DT process. Study 1 investigated the relationship between TD and PM in academic databases, identifying four factors: strategy, project management, skills and digital technologies. Study 2 investigated the digital technologies used in patents in a context that involves TD and PM. The results of study 2 showed that digital technologies demand skills at the individual and collective level to act in scenarios of technological automation, process rationalization, agility, cost reduction and value creation. The combined analysis of studies 1 and 2 allowed the proposition of a conceptual model based on the four identified factors. Therefore, from the theoretical contribution and the proposed conceptual model, study 3 was carried out to verify how the digital transformation process occurs in a company. Study 3 empirically verified the propositions presented in the theoretical model in organizations and, for this, carried out individual interviews to develop a preliminary model and focus groups to validate, receive improvements and give credibility to a final model. Therefore, from the final model, a technological product was developed, and a patent was requested with an invention patent. The development of the technological product is in line with CAPES' determinations for professional doctoral courses, which aim to contribute to technical-scientific advancement. The study has as limitations the fact that it only explores the PM and TD dimensions in a context of Brazilian companies. It is expected that the study will offer theoretical complements to the academy. For practice, the study offers a model to help companies operationalize their TD project, regardless of the company's size and field of activity. In theoretical and academic issues, it is expected that the work will help to understand in depth how the relationship between PM and DT takes place. In the context of TD, PM frameworks are used according to the need and the moment experienced by the company, enabling studies that explore the relationship between PM and TD for the different social contexts of organizations.